Teacher’s conceptions about inclusive education for people with disabilities at EEMTI Dr. José Gondim – Liceu de Iguatu/CE (Research, Society and Development, 2020)
Inclusive education is a policy that recognizes and values diversity as an inherent characteristic of the constitution of any society. In this sense, teacher training has become an extraordinarily active area of intervention and research in recent years. The speeches in favor of this policy, which requires schools to restructure themselves, adapting pedagogical actions to the diversity of learners, have also intensified considerably. Thus, the present study brings a research developed at EEMTDI Dr. Liceu de IGUATU-CE and aims to: analyze the teachers' conceptions about inclusive education of people with disabilities at EEMTI Dr. José Gondim - Liceu de Iguatu / CE; to know the inclusive practices adopted by teachers in that school and to identify the social representations of teachers about the inclusion of disabled people. The research presents a qualitative approach, as Minayo (2012) and its results show that 95% of the teachers develop practical attitudes in terms of inclusion and 56% of these, propose activities that involve social inclusion. On the other hand, the other teachers affirm that they are still unprepared to deal with inclusive education, as they were not prepared to deal with diversity, nor do they have a qualification course in the area of inclusion. Therefore, it is recommended to carry out specialized training in this area, in order to meet the still existing demand, because if the school considered a reference in this type of teaching in the city of this research still presents these gaps, it is likely that in other schools, this training need is even more pronounced.